PENELITIAN EKOLOGI JENIS DURIAN (DURIO SPP.) DI DESA INTUH LINGAU, KALIMANTAN TIMUR - Mansur, Muhammad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Ecological studies on the Durian (Durio spp.) in Intuh Lingau District, East Kalimantan Province was conducted on December 2005. One plot (0,6 ha) was establised at durian habitat for vegetation analysis. As the result, the forest type is secondary forest. Total number of trees (Stem diameter > 10 cm) were 183 individu which dominated by Durio zibethinus, Macaranga triloba, Ficus variegata, Octomeles sumatrana and Strombosia javanica. While, total number of sapling (stem diameter 2-9,9 cm) were 287 individu/0,15 ha which dominated by Leea rubra, Saurauia nudiflora, Monocarpia marginalis and Bridelia glauca. Vegetation structure and composition at study site will also discussed.